Basal Levels and hCG Responses of Serum Testosterone and Estrogen in Male Alpacas - El Zawam, Aymen; Tibary, Ahmed; Patino, Cristian (Frontiers in Veterinary Science, 2020)
Steroid response to human Chorionic Gonadotropin (hCG) administration has been used in various species to study testicular function and for diagnostic purposes. In this study, two experiments were conducted to determine serum testosterone concentration response to administration of hCG and its correlation with testicular weight. In the second experiment the relationship between age, testosterone and estrogenresponse to hCG, and testicular histometry was in prepubertal and postpubertal male alpacas. For experiment 1, males in two age groups (2 to 3 years, n=9) and (4 to 7 years; n= 15) received 3000 IU hCG IV, 36 to 48 hours before castration. Serum testosterone concentration was before (T0), 1hr (T1), 2hr (T2), 8hr (T8) and 24hr (T24) after administration of hCG. Basal concentrations of serum testosterone was significantly different (P<0.01) between age groups. Serum testosterone concentrations increased over time and doubled 2 hr after treatment. The highest change (250 to 300% increase from T0) was observed at 8 hr (3.5 ± 0.3ng/ml). A significant correlation (P < 0.01; r=0.64) was found between serum testosterone concentration and total testicular weight. For experiment 2: 60 males ranging in age from 6 to 60 months were used. Serum testosterone and estrogen was determined in samples taken just prior to and 2 hours after administration of 3000 IU hCG. Basal serum testosterone concentrations were very low (≤0.1ng/mL) until 9 months of age then increased steadily with age. There was a significant variation amongst males within the same age group. Serum testosterone concentration increased by 2 to 4-fold 2 hourse after hCG injection (P ≤0.05). Males in the 13 to14 months of age group had the highest rise. Estrogen concentration increased in response to hCG administration and was detected only in males with high testosterone. We conclude that administration of 3000 IU of hCG IV can be used reliably to detect testicular tissue and study its steroidogenic activity. The response is correlated with testicular weight and Leydig cell number. Testicular growth and sensitivity to LH stimulation increases between the ages of 13 and 14 months. The aromatizing ability of Leydig cells increased significantly in postpubertal male alpacas.